Vaccination Coverage of the Elderly in Greece: A Cross-Sectional Nationwide Study. (28th June 2020) - Papagiannis, Dimitrios; Rachiotis, Georgios; Mariolis, Anargiros; Zafiriou, Efterpi; Gourgoulianis, Konstantinos I.
Abstract : Vaccines are important for older adults, and the morbidity and mortality of vaccine-preventable diseases among older adults are high. There are limited data on vaccination coverage among elderly people in Greece. The aim of this observational study was to record the vaccination coverage for vaccines recommended by the National Vaccination Program in Greece for the elderly people ≥60 years old. Two hundred general practitioners (GPs) around the country from the primary healthcare system were invited to "participate, " and one hundred fifty from them participated in the present study. The GPs were selected using geographically stratified random sampling methodology. Two thousand and seventy-two participants participated in the present study: of which, 1043 were males and 1029 were females. The mean age of the participants was 73.3 years, and 83% vaccination coverage for flu vaccine, 49.5% for conjugate pneumococcal vaccine, and 23.5% for polysaccharide pneumococcal vaccine were recorded. In addition, the vaccination coverage for herpes zoster vaccine was 20%, while very low percentages were recorded for diphtheria, tetanus, pertussis, and polio vaccine for adults. We found significant gaps in vaccination coverage, especially with regard to pneumococcal, herpes zoster, and tetanus. On the contrary, influenza vaccination coverage was satisfactory.